2008
DOI: 10.4161/cc.7.12.6012
|View full text |Cite
|
Sign up to set email alerts
|

A new function of microtubule-associated protein tau: Involvement in chromosome stability

Abstract: Tau is a microtubule-associated protein that promotes assembly and stabilization of cytoskeleton microtubules. It is mostly expressed in neuronal and glial cells but it is also present in non-neural cells such as fibroblasts and lymphocytes. An altered tau produces cytoskeleton pathology resulting in neurodegenerative diseases such as Alzheimer's disease and tauopathies. Tau has been suggested to be a multifunctional protein, due to its localization in different cellular compartments. However its further funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
104
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 33 publications
9
104
0
1
Order By: Relevance
“…The aneuploid and hyperploid neurons that arise in AD are particularly prone to degeneration and could account for 90% of the neuronal loss that characterizes late-stage AD (Arendt et al, 2010). Individuals with Tau P301L mutation, which is associated with frontotemporal dementia, have several chromosome aberrations, such as aneuploidies in their fibroblasts and lymphocytes (Rossi et al, 2008). Consequently, increased level of aneuploidy in splenic lymphocytes of tauopathy transgenic mouse models have recently been reported (Rossi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The aneuploid and hyperploid neurons that arise in AD are particularly prone to degeneration and could account for 90% of the neuronal loss that characterizes late-stage AD (Arendt et al, 2010). Individuals with Tau P301L mutation, which is associated with frontotemporal dementia, have several chromosome aberrations, such as aneuploidies in their fibroblasts and lymphocytes (Rossi et al, 2008). Consequently, increased level of aneuploidy in splenic lymphocytes of tauopathy transgenic mouse models have recently been reported (Rossi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…30,55,56 MT motors are particularly critical in neurons, which must transport vesicles, organelles and molecules, including microtubules themselves over great distances. 57 Indeed, some studies have shown axonal transport to be disrupted in cell and animal models of AD.…”
Section: Discussionmentioning
confidence: 99%
“…However, contradictory in vitro results have shown a protective or deleterious role of Tau in DNA integrity (7)(8)(9). In addition, a recent study reported chromosomal aberrations in fibroblasts and lymphocytes from patients carrying a Tau mutation (10).…”
mentioning
confidence: 99%